2021
DOI: 10.1080/21655979.2021.1902173
|View full text |Cite
|
Sign up to set email alerts
|

Bioprospecting of gut microflora for plastic biodegradation

Abstract: The problem of plastic prevalence and associated pollution has grasped the entire planet drastically, putting all fields of science on the stake seeking remedies to this global havoc. To address this crisis, with a single remediation strategy is often found to be baseless, thereby much interest has been evoked in the development of multidisciplinary approaches -involving physicochemical and biological strategies to nullify the aftermath of plastic pollution in all possible means. Even amidst, the availability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 97 publications
0
14
0
1
Order By: Relevance
“…An undefined group of Capnodiales was present in low abundances only in the plastic treatments and this group differs from that of Aspergillus (Eurotiales). Species found in our study are not frequently reported in the literature regarding mechanical destruction with possible subsequent decomposition by microorganisms ( Cf et al, 2021 ). Similarly to bacterial communities’ patterns, fungal species may differ geographically; but, we suggest that species that were present in all three treatments should be taken as candidate species when describing the core microbiota of G. mellonella .…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…An undefined group of Capnodiales was present in low abundances only in the plastic treatments and this group differs from that of Aspergillus (Eurotiales). Species found in our study are not frequently reported in the literature regarding mechanical destruction with possible subsequent decomposition by microorganisms ( Cf et al, 2021 ). Similarly to bacterial communities’ patterns, fungal species may differ geographically; but, we suggest that species that were present in all three treatments should be taken as candidate species when describing the core microbiota of G. mellonella .…”
Section: Discussionmentioning
confidence: 51%
“…In accordance to our results, Cassone et al (2020) found a dominance of the Proteobacteria phylum in wax moth larvae consuming plastics; but the genera they identified were different from those in this study, except for Pseudomonas . Species of the genus Pseudomonas are among the most cited degraders for a wide range of plastics ( Espinosa et al, 2020 ; Cf et al, 2021 ); they have also been touted for the bioremediation of crude oil, simple hydrocarbons, naphthalene, toluene and other hydrophobic polymers ( Wilkes and Aristilde, 2017 ). The extent to which plastics are biodegraded depends on both the structural arrangement of the polymer and the type of Pseudomonas strain.…”
Section: Discussionmentioning
confidence: 99%
“…and Raoultella ornithinolytica [ 36–38 ]. Similarly, a wide range of xenobiotics such as plastics [ 22 ], hydrocarbons [ 39 ], surfactants [ 40 ], Polychlorinated biphenyls [ 41 ], radioactive waste [ 42 ], heavy metals [ 43 ], etc. are effectively degraded by specific microbes.…”
Section: Role Of Microorganisms In Soil Health Improvementmentioning
confidence: 99%
“…Soil health restoration is a cumulative outcome of indigenous microbes of the lithosphere [ 14 ]. The advantages of relying on microbes are attributed to their versatility to detoxify a wide variety of pollutants [ 15 ], eco-friendly nature [ 16 , 17 ], ability to enrich soil with nutrients [ 18 ], survival in even harsh environments [ 19 , 20 ], production of plant growth-promoting substances [ 21 ], ease of treatment [ 22 ], and absence of toxic end products [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The various microorganisms reported in these biodegradation reports come from dumping grounds, open ocean, seashores, and leftovers from oil refineries due to their property of providing optimum conditions for the microbes to grow and evolve against the high concentration of plastic waste [ 30 ]. Recent reports of mealworm-based plastic assimilation and the role of gut microbiota are pointing toward a large-scale worm-based solution for plastic waste [ 31 ]. There are reports on repurposing the known biocatalysts that degrade similar linker bonds in biopolymers, such as amidase, hydrolase, and esterase, etc.…”
Section: Introductionmentioning
confidence: 99%